Contextualization of Religion and Entrepreneurial Performance: A Lens of Buddhist Small Business Entrepreneurs - Mahadewi, Lufina; Surachman, Surachman; Hadiwidjojo, Djumilah; Indrawati, Nur Khusniyah (Frontiers in Psychology, 2022)
This study explores the manifestation of Buddhism's conception in underlying entrepreneurial performance. The study is a qualitative research approach with a development direction that comes from successful Buddhist small business entrepreneurs in Bekasi, Indonesia. The interpretive paradigm is used to interpret social life in the reality of successful Buddhist small business entrepreneurs on entrepreneurial performance. Data collection using in-depth interviews with Buddhist small business entrepreneurs in an open-ended format. Data analysis was done in many stages, including domain analysis, taxonomy analysis, component analysis, and theme analysis. The findings indicate that religion acts as an institution that legitimizes the formation of entrepreneurial performance. The performance of Buddhist small business entrepreneurs is manifest in their management of economic or material achievements, and their religious observance in a broad socio-economic context in the relationship of three aspects of human life, namely the individual, social, and environmental, as a form of entrepreneurial practice based on Buddhist values. This research reveals the embodiment of social responsibility for small business Buddhist entrepreneurs which is reflected in entrepreneurial performance through the manifestation of religious values. The findings provide theoretical relevance in institutional theory.